2017
DOI: 10.1590/1982-0224-20170067
|View full text |Cite
|
Sign up to set email alerts
|

Estimating population parameters of longsnout seahorses, Hippocampus reidi (Teleostei: Syngnathidae) through mark-recapture

Abstract: Estimating population parameters is essential for understanding the ecology of species, which ultimately helps to assess their conservation status. The seahorse Hippocampus reidi is directly exposed to anthropogenic threats along the Brazilian coast, but the species still figures as Data Deficient (DD) at IUCN's Red List. To provide better information on the ecology of this species, we studied how population parameters vary over time in a natural subtropical environment. By combing mark-recapture models for op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…Other researchers working with larger Hippocampus spp. have had higher recapture rates in focal studies with tagged individuals that could be followed visually over a breeding season, with recapture rates as high as 8%–76% (Correia et al, ; Harasti et al, ; Siqueira et al, ). This individual focal approach is problematic in smaller Hippocampus spp., such as H. zosterae , that are found in dense seagrass beds with little to no visibility of the animals without collection methods such as a seine or push net.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers working with larger Hippocampus spp. have had higher recapture rates in focal studies with tagged individuals that could be followed visually over a breeding season, with recapture rates as high as 8%–76% (Correia et al, ; Harasti et al, ; Siqueira et al, ). This individual focal approach is problematic in smaller Hippocampus spp., such as H. zosterae , that are found in dense seagrass beds with little to no visibility of the animals without collection methods such as a seine or push net.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum height of a species does not appear to vary with latitude, although H. abdominalis exhibited greater height at higher latitudes, which may represent a response to temperature variation . In general, seahorses also do not display differences in size between the sexes Silveira, 2005;Pujol, 2014;Siqueira et al, 2017), as seen in the RS sample. Concerning weight, however, males are expected to be heavier than females, due to the development of the brood pouch (Lovett, 1969;Vincent, 1990;Filleul, 1996;Silveira, 2005;Silveira & Fontoura, 2010).…”
Section: Discussionmentioning
confidence: 76%
“…Among the three species of seahorses that occur in Brazil (Silveira et al, 2014), Hippocampus reidi Ginsburg, 1933, which inhabits marine and estuarine waters, is the most studied (Silveira, 2000(Silveira, , 2005Rosa __________________ Corresponding editor: Yassir Torres et al, 2007;Mai & Velasco, 2011;Silva et al, 2017;Siqueira et al, 2017). Regarding the other two species, Hippocampus erectus Perry, 1810 and Hippocampus patagonicus Piacentino & Luzzatto, 2004, little is known about life history characteristics in Brazilian waters, since none of them are found in estuaries, where seahorses are more accessible and study less expensive than at sea.…”
Section: Introductionmentioning
confidence: 99%
“…The distance moved by seahorses within a specific area, still following a mark‐recapture approach, can, however, provide some insights into site fidelity. Studies have found that seahorses show high site fidelity (Caldwell & Vincent, 2013; Curtis & Vincent, 2006; De La Nuez Hernández et al ., 2016; Harasti et al ., 2014b; Moreau & Vincent, 2004; Siqueira et al ., 2017). Similarly, this study found that H. capensis remained within a relatively small area (~70 m 2 ) for an extended period of time, which emphasises the need to protect this specific habitat from any localised impacts.…”
Section: Discussionmentioning
confidence: 99%